Construction of a Bearing Testing Apparatus to Assess Lifetime of Large-Scale Bearings - Slavomir Hrcek; Vaclav Kraus; Robert Kohar; Stefan Medvecky; Pavol Lehocky (Communications - Scientific letters of the University of Zilina, 2009)
This article discusses steps towards the design, construction and production of a device used for lifetime assessment of large-scale bearings. The machine is reviewed as a mechatronic entity, comprised of three parts - mechanical, electro technical and hydraulic. The mechanical part was designed with the help of modern CAD/CAE/PDM design systems along with device parts modeling and strength analysis of highly stressed device parts. The electrotechnical part consists of a driving unit - containing the frequency transducer and an asynchronous motor; the PLC-driven operating part together with a touchscreen interface and a monitoring part which includes a datalogging device to record measurement results and interface with a PC.